Unlocking Uganda’s Export Potential - National Planning Authority (National Planning Authority, 2018)
Export oriented growth is one of strategies expected to drive Uganda to a lower middle-income status by 2020. However, Uganda’s export performance is shaky, and the efforts and reforms have not yet yielded significant strides in widening the country’s export base. Towards improving Uganda’s export performance, this brief highlights key issues identified in a stakeholder developed Action Plan required for export development. The brief highlights key constraints to Uganda’s export development and also proposes specific actions to address the identified constraints. All these are provided by stakeholders and practitioners around selected priority export products